2007
DOI: 10.1177/0146167207310023
|View full text |Cite
|
Sign up to set email alerts
|

Doing Unto Future Selves As You Would Do Unto Others: Psychological Distance and Decision Making

Abstract: Four experiments showed that the decisions people make for future selves and other people are similar to each other and different from their decisions for present selves. Experiments involved decisions to drink a disgusting liquid for scientific purposes (Experiment 1), tutor peers during exam week (Experiment 2), receive e-mails for charity (Experiment 3), and defer a lottery prize for a larger one (Experiment 4). These findings seemed to be at least partially rooted in the tendency for decisions regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
252
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(277 citation statements)
references
References 33 publications
21
252
0
4
Order By: Relevance
“…Our results help corroborate prior findings in the psychological literature, which, based on paradigms different from the public goods game (Pronin et al, 2008;Sheldon and Fishbach, 2011), are consistent with the idea that the decision to allocate between self and others may be understood as a problem of self-control, between the better judgment to act in the interest of others and the temptation to act in the interest of oneself. We advance the literature in at least three key respects.…”
Section: Resultssupporting
confidence: 90%
“…Our results help corroborate prior findings in the psychological literature, which, based on paradigms different from the public goods game (Pronin et al, 2008;Sheldon and Fishbach, 2011), are consistent with the idea that the decision to allocate between self and others may be understood as a problem of self-control, between the better judgment to act in the interest of others and the temptation to act in the interest of oneself. We advance the literature in at least three key respects.…”
Section: Resultssupporting
confidence: 90%
“…We address the issue in our concluding section. 5 For consistent results in experimental psychology, see Pronin et al (2008) and Sheldon and Fishbach (2011). 5 depleted make lower offers, i.e., they become relatively more selfish. Responders with depleted self-control resources are more likely to reject unfair offers in their study, whereas Halali et al (2011) provide exactly the opposite result for responders.…”
mentioning
confidence: 85%
“…For example, Pronin, Olivola, and Kennedy (2008) found that participants who expected to have to drink a disgusting beverage-an emotionally unpleasant thought-were willing to drink less if the consumption was to occur immediately than if it was to occur in a few months. According to the authors, this is because participants paid more attention to their internal subjective experiences when making decisions involving an immediate consumption than when making decisions involving a more distant consumption-an interpretation that is generally consistent with our notion of a greater reliance on affective feelings when outcomes are proximate.…”
Section: Our Specific Hypothesismentioning
confidence: 99%
“…Therefore, any departure (or distance) from this egocentric self-whether in time, space, social closeness, or reality-would tend to decrease the reliance on affect in judgments. Preliminary support for this conjecture comes from studies showing that (a) emotional involvement decreases as a function of physical distance (Bratfisch 1969;Stanley 1968); (b) affective intensity decreases as a function of perceived psychological distance (Van Boven et al 2010); (c) the mere priming of physical distance decreases the influence of affect on judgments (Williams and Bargh 2008); affective feelings exert a stronger influence on judgments and decisions made for oneself than on judgments and decisions made for someone else (Pronin et al 2008;Raghunathan and Pham 1999). …”
Section: Generalizability Across Dimensions Of Psychological Distancementioning
confidence: 99%